2011
DOI: 10.1016/j.jff.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of l-theanine on attention and reaction time response

Abstract: Attention Reaction response Relaxation A B S T R A C TPrevious human studies revealed that L-theanine influences brain function. The current study was designed to evaluate the affect of L-theanine (Suntheanine â ) on attention and reaction time response in 18 normal healthy University student volunteers. In accordance with preliminary analysis of the manifest anxiety scale (MAS), the subjects were divided into two groups referred to as high anxiety propensity group and the minimal anxiety propensity group. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 34 publications
4
34
0
Order By: Relevance
“…This finding goes in line with the caffeine related improved performance in the Berg's Card Sorting Test (BCST) and simple reaction time tasks and supports previous findings that showed caffeine induced facilitation of attention [32,44] and level of alertness [13,45]. It is also consistent with other previous studies [2,16,19,38] that linked consumption of tea to robust increases in alertness and information processing capacity [4]. As cholinergic mechanisms have been shown to be a necessary condition for memory formation in rats [46], we hypothesize that BT might also be able to influence the level of cholinergic mechanisms in humans, thus improving memory formation [46].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding goes in line with the caffeine related improved performance in the Berg's Card Sorting Test (BCST) and simple reaction time tasks and supports previous findings that showed caffeine induced facilitation of attention [32,44] and level of alertness [13,45]. It is also consistent with other previous studies [2,16,19,38] that linked consumption of tea to robust increases in alertness and information processing capacity [4]. As cholinergic mechanisms have been shown to be a necessary condition for memory formation in rats [46], we hypothesize that BT might also be able to influence the level of cholinergic mechanisms in humans, thus improving memory formation [46].…”
Section: Discussionsupporting
confidence: 92%
“…Caffeine improves low alertness during long drive [14]. Besides caffeine, Theanine improves attentional performance at a dose of 200 mg/100 ml water [19]. Important to notice, effect of caffeine is shown to be related to the habitual intake levels.…”
Section: Introductionmentioning
confidence: 92%
“…[3] and Higashiyama et al . [23]; and 250 mg in Gomez-Ramirez et al . [24]), the low dose of 52 mg in shaded white tea in this study might have been insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the effects of L-THE on learning ability and on a multitude of neuroprotective effects ( Table 2) [8]. One specific study, involving administration of L-THE (200 mg/100 mL water), reported profound effects on attention performance as well as on reaction time responses in normal healthy subjects prone to high anxiety [59]. There is also evidence to support its synergistic relationship with caffeine.…”
Section: Effect Of L-the On Cognition and Learning Abilitymentioning
confidence: 99%